Effect of non-genetic factors on incidence of lameness in Karan Fries cross bred cows - GUPTA, RAVI KANT; LATHWAL, S S; RUHIL, A P; DASH, S K; SINGH, MAN (The Indian Journal of Animal Sciences, 2016)
Effect of period and season of calving had significant effect on incidence of lameness while effect of parity and lactation yield on incidence of lameness was not significant. It was found that high yielder cows and cows in early stage of lactation were highly affected with the lameness as compare to low yielder cows and cows in succeeding stages of lactation. Though, non-genetic factors certainly have effect on incidence of lameness but better managemental interventions at farm level can play a key role in minimizing these effects.